Familial Creutzfeldt-Jakob Disease: Case report and role of genetic counseling in post mortem testing. Issue 6 (1st November 2016) - Clift, Kristin; Guthrie, Kimberly; Klee, Eric W.; Boczek, Nicole; Cousin, Margot; Blackburn, Patrick; Atwal, Paldeep
ABSTRACT: Here we present a case of an asymptomatic 53-year-old woman who sought genetic testing for Familial Creutzfeldt-Jakob Disease (fCJD) after learning that her mother had fCJD. The patient's mother had a sudden onset of memory problems and rapidly deteriorating mental faculties in her late 70s, which led to difficulties ambulating, progressive non-fluent aphasia, dysphagia and death within ∼1 y of symptom onset. The cause of death was reported as "rapid onset dementia." The patient's family, unhappy with the vague diagnosis, researched prion disorders online and aggressively pursued causation and submitted frozen brain tissue from the mother to the National Prion Disease Surveillance Center, where testing revealed a previously described 5-octapeptide repeat insertion (5-OPRI) in the prion protein gene ( PRNP ) that is known to cause fCJD. The family had additional questions about the implications of this result and thus independently sought out genetic counseling. While rare, fCJD is likely underdiagnosed due to clinical heterogeneity, rapid onset, early non-specific symptomatology, and overlap in the differential diagnosis of Alzheimer disease and Lewy body dementias. When fCJD is identified, a multidisciplinary approach to return of results that includes the affected patient's provider, genetics professionals, and mental health professionals is key to the care of the family. We present an example case which discusses the psychosocial issues encountered and the role of genetic counseling in presymptomatic testing for incurable neurodegenerative conditions. Ordering physicians should be aware of the basic issues surrounding presymptomatic genetic testing and identify local genetic counseling resources for their patients.